Analysis of the Internal Force and Deformation Characteristics of Double-Layer Lining Structure of Water Conveyance Tunnel. (30th April 2022) - Yueyue Zhu,; Cheng Liu,; Xiaotian Yin,; Jingyu Zhang,
Abstract : Shield double-layer lining structure is used to bear large internal water pressure in water conveyance tunnel engineering, but the mechanism of joint stress of structure and force transmission between linings is still unclear. In this paper, a stress calculation model of the double-layer lining structure of shield water conveyance tunnel considering the influence of transition layer between the inner lining and the outer lining is presented. By analyzing the inner lining and outer lining separately, the calculation formulas of radial displacement and circumferential stress are obtained. Then, according to the deformation coordination condition, the relationship between the inner and outer lining radial displacements is established. Thus, the magnitude of the unknown interaction force among the structures is calculated. Finally, through the stress analysis of the lining structure, the axial force, shear force, and bending moment acted on the structure are obtained. By comparing finite element calculation results with analytical calculation results, the rationality of analytical solutions is verified. Based on the proposed analytical method, the influence of inner lining thickness and material parameters of transition layer on the internal force and deformation of lining structure is analyzed. The results show that with the increase of the thickness of the inner lining, the axial force and bending moment increase, while the internal pressure shared by the outer lining decreases. The larger the elastic modulus of the transition material, the smaller the difference between the internal force and deformation of the inner and outer linings.